The development of Practical Skills and Academic Achievement on Editing Graphics Using the 5-Steps GPAS Process with Multimedia of the Second year Vocational Certificate Students - Papun, Lalai; Kongnavang, Sangdun (NEU ACADEMIC AND RESEARCH JOURNAL, 2022)
The objectives of this research were (1) to compare of the practical skills ability of the 2nd vocational students on the subject titled Editing graphics using learning management with GPAS 5 Steps process together with multimedia before and after learning, (2) to compare learning achievement on the subject titled Editing graphics by using learning management with GPAS 5 Steps process together with multimedia before and after learning and (3) to study the satisfaction of the 2nd vocational students on the subject titled Editing graphics by using learning management with GPAS 5 Steps process together with multimedia. The target group consisted of the 2nd vocational students in Business Computer department, 2nd semester of academic year 2018, Eastern Technological College. The research tools included: 1) 4 learning management plans 16 hours by using GPAS 5 Steps process together with multimedia 2) A practical skill assessment form using learning management with GPAS 5 Steps process together with multimedia 3) Educational achievement assessment form, 4) Students’ questionnaire on the subject titled Editing graphics by using learning management with GPAS 5 Steps process together with multimedia. The statistics used to analyze data comprised mean, percentage, standard deviation and t-test dependent sample. The research results were found that (1) The assessment results of the practical skills of the 2nd vocational students on the subject titled Editing graphics by using learning management with GPAS 5 Steps process together with multimedia were rated at 15.82 and 20.44 points. The results of comparison of pre-test and post-test scores were found that they were significantly higher than before learning at .01 level. (2) Learning achievement on the subject titled Editing graphics by using learning management with GPAS 5 Steps process together with multimedia before and after learning was = 17.31 and 22.73 respectively, the post-test score was significantly higher than pre-test at .01 level. (3) The students’ satisfaction towards the teaching and learning activity on the subject titled Editing graphics by using learning management with GPAS 5 Steps process together with multimedia, in overall, was at the highest level with the rate of 4.33.